S->Sa/a here to convert into LL(1) need to be remove left recursive

for this S->ab/a here to convert LL(1) remove left factoring

then if i take a grammer which not having both left recursive and left factoring for example S->AB/a ;A->a,B->epsilon then but still not parse by LL(1) bcz it is ambiguous so for that we have to be fulfill all three condition then we can convert into LL(1) surely so D

for this S->ab/a here to convert LL(1) remove left factoring

then if i take a grammer which not having both left recursive and left factoring for example S->AB/a ;A->a,B->epsilon then but still not parse by LL(1) bcz it is ambiguous so for that we have to be fulfill all three condition then we can convert into LL(1) surely so D